Heat shrinkable multilayer film and method for producing same

JP7641896B2Active Publication Date: 2025-03-07DENKA CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021530725
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-11
Filing Date
2020-07-09
Publication Date
2025-03-07
Estimated Expiration
2040-07-09

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、フィルム強度、透明性、耐自然収縮性、フィルム剛性といった諸物性を維持しつつ、従来よりも耐溶剤性に優れ、また良好な熱収縮仕上がり性を有する熱収縮性多層フィルム及びその製造方法を提供できる。また、前記熱収縮性多層フィルムを備える熱収縮性ラベル、前記熱収縮性ラベルを熱収縮させて得られるラベル及びその製造方法を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641896000004
    Figure 0007641896000004
  • Figure 0007641896000001
    Figure 0007641896000001
  • Figure 0007641896000002
    Figure 0007641896000002
Patent Text Reader

Abstract

[Problem] To provide: a heat-shrinkable multilayer film having superior solvent resistance in comparison to the prior art and good heat-shrink finish properties while maintaining various physical properties such as film strength, transparency, natural shrinkage resistance, and film rigidity; and a method for producing the same. In addition, to provide: a heat-shrinkable label having the heat-shrinkable multilayer film; a label obtained by thermally shrinking the heat-shrinkable label; and a method for producing the same. [Solution] This heat-shrinkable multilayer film having at least two types of layers contains a block copolymer resin (I) including a vinyl aromatic hydrocarbon monomer unit (Xi) and a conjugated diene monomer unit (Yi) in at least one surface layer of the heat-shrinkable multilayer film, wherein the block copolymer resin (I) satisfies a specific constituent of (i-1) to (i-4).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat-shrinkable multilayer film and a method for producing the same. The present invention also relates to a heat-shrinkable label made using the heat-shrinkable multilayer film, a label obtained by heat-shrinking the heat-shrinkable label, and a method for producing the same. [Background technology]

[0002] A heat-shrinkable film is a film that has the property of shrinking when heated, and is used, for example, for shrink packaging, etc. When a heat-shrinkable film is used for shrink packaging, the heat-shrinkable film, which has been printed as necessary, is temporarily attached to one or all of the surface of the packaged object, and then heat-shrunk to fit closely to the shape of the packaged object. Heat-shrinkable labels, which are made by further applying printing or the like to the surface of a heat-shrinkable film, are widely used for labels on beverage containers such as PET bottles, and are also called shrink labels. In recent years, as the physical properties required of heat-shrinkable films have become more sophisticated, heat-shrinkable multilayer films having a multilayer structure in which multiple layers with different properties and chemical compositions are laminated have been proposed.

[0003] The physical properties required for a heat-shrinkable film include, for example, film transparency to make the most of the printed design of the shrink label, resistance to natural shrinkage, etc. Here, "resistance to natural shrinkage" refers to a physical property that makes it difficult for the heat-shrinkable film to unintentionally shrink (natural shrinkage) when stored or transported in an environment with insufficient temperature control. Other physical properties required for a heat-shrinkable film include, for example, film rigidity to prevent the shrink label itself from bending due to its own weight when a sleeve-shaped shrink label is temporarily attached to a beverage container such as a PET bottle (before heat shrinking), and heat-shrink finish to prevent wrinkles, slackness, bending, etc. that occur in the film during heat shrinking and remain after shrinkage.

[0004] As heat-shrinkable films that can satisfy the above-mentioned various physical properties, for example, Patent Documents 1 to 3 describe heat-shrinkable films produced using a resin containing a block copolymer having a specific chemical structure, which is composed of vinyl aromatic hydrocarbon monomer units and conjugated diene monomer units.

[0005] In recent years, beverage containers such as PET bottles used as packaging materials for heat-shrinkable films have become more diverse and complex in shape in order to improve their design, and the heat-shrinkable films used to shrink-wrap these containers are required to have a higher level of heat-shrink finish. Furthermore, as shrink labels have become thinner in recent years, they are more susceptible to the effects of organic solvents (hereinafter sometimes simply referred to as "solvents") contained in printing inks, such as a decrease in film strength, and there is a greater demand for resistance to organic solvents in the ink on the printed surface (hereinafter referred to as "solvent resistance") than ever before. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2005-213520 A [Patent Document 2] JP 2003-313259 A [Patent Document 3] International Publication No. 2012 / 117964 Summary of the Invention [Problem to be solved by the invention]

[0007] Therefore, an object of the present invention is to provide a heat-shrinkable multilayer film that has better solvent resistance than conventional films and has good heat-shrink finish while maintaining various physical properties such as film strength, transparency, natural shrinkage resistance, and film rigidity, and a method for producing the same. Another object of the present invention is to provide a heat-shrinkable label comprising the heat-shrinkable multilayer film, a label obtained by heat-shrinking the heat-shrinkable label, and a method for producing the same. [Means for solving the problem]

[0008] That is, the present invention has the following aspects. [1] A heat-shrinkable multilayer film having at least two layers, Vinyl aromatic hydrocarbon monomer unit (X i ) and conjugated diene monomer units (Y i At least one surface layer of the heat-shrinkable multilayer film contains a block copolymer resin (I) containing The block copolymer resin (I) satisfies the following (i-1) to (i-4): (i-1) The vinyl aromatic hydrocarbon monomer unit (X i ) and the conjugated diene monomer unit (Y i ) and the total (100 mass%) of the vinyl aromatic hydrocarbon monomer units (X i ) is 60% by mass or more and 82% by mass or less, and the conjugated diene monomer unit (Y i ) is 18 mass % or more and 40 mass % or less. (i-2) Weight average molecular weight (Mw i ) is between 100,000 and 300,000. (i-3) In dynamic viscoelasticity measurement, the loss tangent (tanδ) value was measured at a heating rate of 4°C / min, a frequency of 1Hz, and in the temperature range from room temperature to 130°C. i ) has at least one maximum value in the temperature range, and the loss tangent value (tan δ i ) is the maximum temperature T i (℃) is in the temperature range of 90℃ or more and 120℃ or less. (i-4) The vinyl aromatic hydrocarbon monomer unit (X i ) as the main component, and the conjugated diene monomer unit (Y i The soft phase, which is mainly composed of cellulose acetate, has a microphase separation structure with a lamellar structure. [2] The heat-shrinkable multilayer film according to [1], wherein the block copolymer resin (I) is a block copolymer resin containing a block copolymer having a branched structure. [3] Vinyl aromatic hydrocarbon monomer unit (X ii ) and conjugated diene monomer units (Y ii In at least one layer other than the surface layer containing the block copolymer resin (I), The heat-shrinkable multilayer film according to [1] or [2], wherein the block copolymer resin (II) satisfies the following (ii-1) to (ii-3): (ii-1) The vinyl aromatic hydrocarbon monomer unit (X ii ) and the conjugated diene monomer unit (Y ii ) relative to the total (100 mass%) of the vinyl aromatic hydrocarbon monomer units (X ii ) is 70% by mass or more and 84% by mass or less, and the conjugated diene monomer unit (Y ii ) is 16 mass % or more and 30 mass % or less. (ii-2) Weight average molecular weight (Mw ii ) is between 100,000 and 300,000. (ii-3) In dynamic viscoelasticity measurement, the loss tangent (tanδ) value measured at a heating rate of 4°C / min, a frequency of 1Hz, and a temperature range of room temperature to 130°C ii ) has at least one maximum value in the temperature range, and the loss tangent value (tan δ ii ) is the maximum temperature T ii (℃) is T i In relation to (°C), the following formulas (1) and (2) are satisfied. T i >T ii (1) 15≦(T i -T ii )≦35 (2) [4] The heat-shrinkable multilayer film according to [3], wherein the block copolymer resin (II) is a block copolymer resin containing a block copolymer having a branched structure. [5] The heat-shrinkable multilayer film according to any one of [1] to [4], wherein the maximum heat shrinkage rate in the MD direction in the temperature range of 70°C or higher and 100°C or lower is 5% or lower and the minimum heat shrinkage rate is -3% or higher. [6] The heat-shrinkable multilayer film according to any one of [1] to [5], having a heat shrinkage rate in the TD direction of 30% or more at 80°C and a heat shrinkage rate in the TD direction of 65% or more at 100°C. [7] A method for producing a heat-shrinkable multilayer film according to any one of [1] to [6], further comprising the steps of: (a) determining a loss modulus (E″) of the block copolymer resin (I) measured in a dynamic viscoelasticity measurement of an unstretched multilayer film containing the block copolymer resin (I) in at least one surface layer at a heating rate of 4° C. / min, a frequency of 1 Hz, and a temperature range of room temperature to 130° C.; i ) is the maximum temperature T ic For (T ic -25)℃ or higher (T ic stretching the unstretched multilayer film in the MD direction at a ratio of 1.00 to 1.30 and in the TD direction at a ratio of 3.0 to 8.0 at a temperature range of +15°C or lower. [8] A heat-shrinkable label comprising the heat-shrinkable multilayer film according to any one of [1] to [6]. [9] A method for producing a label by heat-shrinking the heat-shrinkable label described in [8]. Effect of the Invention

[0009] According to the present invention, it is possible to provide a heat-shrinkable multilayer film having better solvent resistance than conventional films and good heat-shrink finish while maintaining various physical properties such as film strength, transparency, natural shrinkage resistance, and film rigidity, and a method for producing the same. It is also possible to provide a heat-shrinkable label including the heat-shrinkable multilayer film, a label obtained by heat-shrinking the heat-shrinkable label, and a method for producing the same. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view showing one embodiment of a heat-shrinkable multilayer film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described in detail. However, the present invention is not limited to the following embodiment, and can be carried out by making appropriate changes within the scope that does not impair the effects of the present invention.

[0012] [Heat-shrinkable multi-layer film] The heat-shrinkable multilayer film according to an embodiment of the present invention is a heat-shrinkable multilayer film having at least two types of layers, i ) and conjugated diene monomer units (Y i ), and the block copolymer resin (I) containing the above-mentioned and the above-mentioned block copolymer resin (I) satisfies the following (i-1) to (i-4). (i-1) The vinyl aromatic hydrocarbon monomer unit (X i ) and the conjugated diene monomer unit (Y i ) and the total (100 mass%) of the vinyl aromatic hydrocarbon monomer units (X i ) is 60% by mass or more and 82% by mass or less, and the conjugated diene monomer unit (Y i ) is 18 mass % or more and 40 mass % or less. (i-2) Weight average molecular weight (Mw i ) is between 100,000 and 300,000. (i-3) In dynamic viscoelasticity measurement, the loss tangent (tanδ) value was measured at a heating rate of 4°C / min, a frequency of 1Hz, and in the temperature range from room temperature to 130°C. i ) has at least one maximum value in the temperature range, and the loss tangent value (tan δ i ) is the maximum temperature T i (℃) is in the temperature range of 90℃ or more and 120℃ or less. (i-4) The vinyl aromatic hydrocarbon monomer unit (X i ) as the main component, and the conjugated diene monomer unit (Y i The soft phase, which is mainly composed of cellulose acetate, has a microphase separation structure with a lamellar structure. FIG. 1 is a cross-sectional view showing one embodiment of the heat-shrinkable multilayer film of the present invention. The heat-shrinkable multilayer film 10 has a surface layer 1 and a surface layer 2. The heat-shrinkable multilayer film of the present invention has a vinyl aromatic hydrocarbon monomer unit (X i ) and conjugated diene monomer units (Y i ) and a block copolymer resin (I).

[0013] <Surface layer> The heat-shrinkable multilayer film of the present invention has at least two kinds of layers, and at least one of the surface layers contains a block copolymer resin (I). In the present invention, "two kinds of layers" means two kinds of layers with different compositions. In the present invention, "surface layer" means the outermost layer of the heat-shrinkable multilayer film. In one use form of the present invention, printing or coating may be further performed on the surface layer, but these are not included in the "layer" of the present invention. In general, in shrink labels, inner printing is performed by performing printing on the surface layer on the side that contacts the packaged article (for example, a beverage container such as a PET bottle). In one embodiment of the present invention, it is preferable that the surface layer on the side on which printing is performed contains a block copolymer resin (I), and it is more preferable that both surface layers contain a block copolymer resin (I). In one embodiment of the present invention, the surface layer is preferably composed of a block copolymer resin (I). As described later, the block copolymer resin (I) may contain an optional component.

[0014] <Layers other than the surface layer (intermediate layer)> In the present invention, when the heat-shrinkable multilayer film of the present invention is composed of three or more layers, the layers other than the surface layer are referred to as "intermediate layers". In one preferred embodiment of the present invention, the intermediate layer contains a block copolymer resin (II). The total number of layers in the heat-shrinkable multilayer film can be appropriately selected depending on the intended use, but from the viewpoint of productivity, it is preferable that the heat-shrinkable multilayer film is composed of two kinds of three layers, in which the same surface layers are provided on both sides of a single intermediate layer, and the thickness ratio (total thickness of both surface layers / thickness of intermediate layer) is preferably 10 to 50 / 50 to 90 relative to the total thickness (100).

[0015] (Block copolymer resin (I)) The heat-shrinkable multilayer film according to the present embodiment is a film containing a vinyl aromatic hydrocarbon monomer unit (X i ) and conjugated diene monomer units (Y i ) is contained in at least one surface layer of the heat-shrinkable multilayer film, and the block copolymer resin (I) satisfies the above (i-1) to (i-4).

[0016] In this embodiment, the block copolymer resin (I) contains a vinyl aromatic hydrocarbon monomer unit (X i ) and conjugated diene monomer units (Y i In one embodiment of the present invention, the block copolymer resin (I) is preferably one obtained by anionic polymerization of a vinyl aromatic hydrocarbon and a conjugated diene. The block copolymer resin (I) may be composed of one type of block copolymer or a mixture of two or more types of block copolymers, so long as it satisfies the above (i-1) to (i-4) as a whole.

[0017] Here, "one type of block copolymer" refers to a block copolymer obtained, for example, by using vinyl aromatic hydrocarbon and conjugated diene as main raw materials and completing the polymerization with only one initiation reaction and one termination reaction by batch-type anionic polymerization (hereinafter, sometimes simply referred to as "polymerization"). Strictly speaking, unintended deactivation of anionic polymerization activity may occur during the polymerization, resulting in a small amount of polymers with different molecular weights and chemical structures being by-produced, but such polymers are not included.

[0018] Furthermore, the term "two or more types of block copolymers" refers to a mixture of multiple types of block copolymers obtained, for example, in anionic polymerization, when multiple initiation reactions are performed other than the initial initiation reaction, when multiple termination reaction operations are performed, when a coupling reaction operation is performed during anionic polymerization, or when these operations are further combined, or a block copolymer obtained by mixing two or more types of block copolymers produced by polymerization of different batches.

[0019] In the block copolymer resin (I), the vinyl aromatic hydrocarbon unit (X i ) and conjugated diene monomer units (Y i ) (block copolymers having the same basic molecular chain structure) can be treated as the same type. Note that block copolymers of the same type may have unavoidable molecular weight variations associated with the polymerization reaction. Although the molecule of the block copolymer resin (I) is called a "block copolymer," the "block" contained therein does not necessarily have to be a "block" composed of a single monomer unit of either vinyl aromatic hydrocarbon or conjugated diene. i ) as the main component, a hard phase is formed, and i) as the main component, a soft phase is formed. The block copolymer molecule may contain unit components derived from a polymerization initiator or a coupling agent, which will be described later. Hereinafter, in this specification, vinyl aromatic hydrocarbons and conjugated dienes may be collectively referred to as "main raw materials," and other raw materials related to the production may be collectively referred to as "auxiliary raw materials."

[0020] (Vinyl aromatic hydrocarbon monomer unit (X i ), conjugated diene monomer units (Y i )) As used herein, the term "vinyl aromatic hydrocarbon monomer unit (X i )" (hereinafter referred to as "monomer unit (X i )) refers to a structural unit based on vinyl aromatic hydrocarbon in the molecular chain of the block copolymer resin (I). Similarly, "conjugated diene monomer unit (Y i ) (hereinafter referred to as "monomer unit (Y i )) means a structural unit based on a conjugated diene in the molecular chain of the block copolymer resin (I).

[0021] Examples of vinyl aromatic hydrocarbons include styrene, o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, α-methylstyrene, vinylnaphthalene, vinylanthracene, etc. Among them, at least one selected from the group consisting of styrene and α-methylstyrene is preferred.

[0022] Examples of the conjugated diene include 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, etc. Among them, at least one selected from the group consisting of 1,3-butadiene and isoprene is preferable.

[0023] The block copolymer resin (I) can be obtained by a known method such as that shown in JP-A-2003-313259. Specifically, according to a recipe for forming the molecules and composition of the target block copolymer resin (I), the vinyl aromatic hydrocarbon and the conjugated diene are added to a polymerization reaction system, either singly or simultaneously, in the presence of a polymerization initiator, and anionic polymerization is carried out to obtain the block copolymer resin (I). Examples of the method for adding the vinyl aromatic hydrocarbon and the conjugated diene include lump-sum addition, in which the entire amount is added at once, successive addition, in which the amount is added in several portions, and portion-wise addition, in which the amount is added continuously at a constant flow rate.

[0024] A more specific example of the method for producing the block copolymer resin (I) includes a method in which, after thorough dehydration, a vinyl aromatic hydrocarbon and a conjugated diene are anionically polymerized using an organolithium compound as a polymerization initiator in an organic solvent in which a randomizer is coexistent as necessary, and the polymerization is completed by a deactivation treatment, and then the organic solvent is removed to obtain the block copolymer resin (I).

[0025] Examples of the organic solvent that can be used include aliphatic hydrocarbons such as butane, pentane, hexane, isopentane, heptane, octane, and isooctane, alicyclic hydrocarbons such as cyclohexane, methylcyclohexane, and ethylcyclohexane, and aromatic hydrocarbons such as benzene, toluene, ethylbenzene, and xylene. Of these, cyclohexane is preferred.

[0026] The organolithium compound is an organic compound having one or more lithium atoms bonded in the molecule, and can be, for example, monofunctional organolithium compounds such as ethyllithium, n-propyllithium, n-butyllithium, sec-butyllithium, tert-butyllithium, etc., which generate one polymerization active terminal per molecule, as well as polyfunctional organolithium compounds (polyfunctional organolithium compounds) such as hexamethylenedilithium, butadienyldilithium, isoprenyldilithium, etc. Among the above, n-butyllithium is preferred. The timing of adding the polymerization initiator may be added all at once at the beginning of the polymerization, or it may be added during the polymerization.

[0027] The randomizer is a compound for adjusting the reactivity ratio of vinyl aromatic hydrocarbon and conjugated diene to the active terminal of anionic polymerization. As the randomizer, for example, tetrahydrofuran (THF) is preferably used, but other than that, ethers, amines, thioethers, phosphoramide, alkylbenzenesulfonate, potassium or sodium alkoxide, etc. can also be used. Examples of ethers include dimethyl ether, diethyl ether, diphenyl ether, diethylene glycol dimethyl ether, and diethylene glycol dibutyl ether. Examples of amines include tertiary amines such as trimethylamine, triethylamine, and tetramethylethylenediamine, as well as cyclic amines. Other examples of randomizers that can be used include triphenylphosphine, hexamethylphosphoramide, potassium or sodium alkylbenzenesulfonate, and potassium or sodium butoxide.

[0028] The amount of these randomizers to be added is 10 parts by mass or less, preferably 0.001 to 8 parts by mass, per 100 parts by mass of the total amount of vinyl aromatic hydrocarbon and conjugated diene. The addition may be made before the start of the polymerization reaction or during the polymerization. In addition, the randomizer may be additionally added as necessary.

[0029] (Block copolymer resin (I) containing a branched structure) For example, when only a monofunctional polymerization initiator such as n-butyl lithium is used, the block copolymer resin (I) forms a linear chemical structure (straight-chain structure) without branches, and the polymerization reaction can be completed by adding a polymerization terminator in an amount sufficient to deactivate the active terminals of the anionic polymerization. In this case, each molecule of the block copolymer resin (I) has a straight-chain structure. On the other hand, when a compound called a coupling agent is further added and reacted in a state in which all or part of the active terminals of the anionic polymerization of the molecule are present (living state) in the intermediate stage of polymerization, or when a polyfunctional polymerization initiator having three or more functionalities is used, all or part of the molecules of the block copolymer resin (I) have a branched structure.

[0030] The block copolymer resin (I) according to the present invention may have either a linear or branched molecular structure, or may have both a linear and branched molecular structure. In one embodiment of the present invention, the molecular structure of the block copolymer resin (I) preferably contains a branched structure, and more preferably contains both a linear and branched structure. When the block copolymer resin (I) contains a branched structure, the solvent resistance of the heat-shrinkable multilayer film becomes better. The presence or absence of a branched structure in the block copolymer resin (I) can be confirmed by, for example, gel permeation chromatography (GPC) or an analytical method that combines GPC with a multi-atom laser light scattering detector (MALS).

[0031] As the coupling agent, for example, a compound having three or more functional groups, which is at least one type of functional group selected from the group consisting of an epoxy group, an ester group, a carboxy group, a ketone group, a vinyl group, a chlorosilyl group, and a silyl ether group, can be used. Among them, tetrachlorosilane, tetraalkoxysilane, vinyltrichlorosilane, vinyltrialkoxysilane, epoxidized soybean oil, epoxidized linseed oil, etc. can be generally used, and among them, epoxidized soybean oil, epoxidized linseed oil, and tetraalkoxysilane are preferred. As for the form of addition, the coupling agent may be added alone, or the coupling agent diluted with the dehydrated organic solvent may be added.

[0032] The active terminals of the anionic polymerization are inactivated by adding a polymerization terminator such as water, alcohol, or carbon dioxide in an amount sufficient to inactivate the polymerization active terminals. The polymerization is finally completed by the above process to form a block copolymer resin (I). However, in this case, the block copolymer resin (I) exists in a state of being dissolved in an organic solvent. Therefore, a process of removing the organic solvent is provided to obtain the block copolymer resin (I) in a form that is generally easy to use. The organic solvent can be removed by any method, such as a method in which the organic solvent containing the block copolymer resin (I) is poured into a poor solvent such as methanol to precipitate and separate the block copolymer resin (I) (reprecipitation method), a method in which the organic solvent is evaporated using a heated roll or the like to precipitate the block copolymer resin (drum dryer method), a method in which the organic solution is concentrated using a concentrator and then the organic solvent is removed by degassing and extruding using, for example, a vented extruder (degassing extrusion method), or a method in which the organic solvent containing the block copolymer resin (I) is dispersed in warm water and then steam is blown in to heat and remove the organic solvent (steam stripping method).

[0033] In the present invention, if necessary, the block copolymer resin (I) may further contain other resins and various additives within a range that does not impair the requirements and effects of the present invention. In this specification, the block copolymer resin (I) also refers to the resin containing the other resins and various additives.

[0034] (Other resins) The block copolymer resin (I) may contain other resins as necessary within a range that does not impair the various physical properties required for the heat shrinkable multilayer film according to the embodiment of the present invention. Specifically, at least one polymer selected from the vinyl aromatic hydrocarbon polymers (a) to (d) shown below, polyolefin (PO), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polycarbonate (PC), polyamide (PA), polyvinyl chloride (PVC), polyacetal (POM), polyvinyl alcohol (PVA), ethylene-vinyl alcohol copolymer (EVOH), etc. may be contained. These other resins may be mixed in an amount of 50% by mass or less, preferably 30% by mass or less, and more preferably 25% by mass or less, based on the total mass of the block copolymer resin (I). If the amount exceeds 50% by mass, the physical properties such as transparency, strength, and heat shrinkability tend to decrease, and the object of the present invention cannot be achieved. (a) Vinyl aromatic hydrocarbon polymer (b) A copolymer of vinyl aromatic hydrocarbon and (meth)acrylic acid ester (c) Vinyl aromatic hydrocarbon-conjugated diene-(meth)acrylic acid ester copolymer (d) Hydrogenated block copolymers of vinyl aromatic hydrocarbons and conjugated dienes

[0035] (a) Examples of the vinyl aromatic hydrocarbon polymer include polystyrene, poly-α-methylstyrene, and syndiotactic polystyrene. Among these, polystyrene such as general-purpose polystyrene (GPPS) can be preferably used.

[0036] The vinyl aromatic hydrocarbons and conjugated dienes used in the copolymers (b) to (d) are preferably compounds that can be used as the main raw materials for the block copolymer resin (I).

[0037] Examples of the (meth)acrylic acid ester used in each of the copolymers (b) and (c) include methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, isoamyl acrylate, n-hexyl acrylate, (2-ethyl)hexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, and (2-ethyl)hexyl methacrylate.

[0038] (d) Hydrogenated block copolymers of vinyl aromatic hydrocarbons and conjugated dienes include hydrogenated block copolymers containing a hard block mainly composed of vinyl aromatic hydrocarbons and a soft block mainly composed of conjugated dienes. The hydrogenated block copolymers can be obtained, for example, by hydrogenating the block copolymers obtained by polymerization according to a known method in the presence of a catalyst. As the catalyst, for example, nickel, ruthenium, palladium, and platinum catalysts are generally used, and titanocene compounds or reducing organometallic compounds can also be used.

[0039] (Various additives) Typical types of additives that can be contained in the block copolymer resin (I) include antioxidants (heat stabilizers), ultraviolet absorbers (weather resistance agents), lubricants, plasticizers, antistatic agents, antifogging agents, antiblocking agents, colorants, and the like.

[0040] Examples of the antioxidant that can be used include phenol-based antioxidants such as 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, and n-octadecyl-3-(4-hydroxy-3,5-di-tert-butylphenyl)propionate; and phosphorus-based antioxidants such as 2,2'-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite and tris(2,4-di-tert-butylphenyl)phosphite.

[0041] Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers such as 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole, triazine-based ultraviolet absorbers such as 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol, and hindered amine-type weathering agents such as tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate. White oil, silicone oil, and the like can also be added.

[0042] Examples of lubricants include fatty acids, fatty acid esters, fatty acid amides, glycerin fatty acid esters (glycerides), sorbitan fatty acid esters, pentaerythritol fatty acid esters, sucrose fatty acid esters, propylene glycol fatty acid esters, as well as polyolefin waxes such as polyethylene wax and polypropylene, paraffin wax, microcrystalline wax, petrolatum, and the like.

[0043] As the plasticizer, liquid paraffin is generally used, and organic acid esters such as adipic acid esters can also be used.

[0044] As the antistatic agent, surfactants such as nonionic surfactants, anionic surfactants, cationic surfactants, amphoteric surfactants, etc. are mainly used. They may be kneaded into the resin before use, or may be formed into various films and then coated on the surface.

[0045] As the antifogging agent, in addition to the above-mentioned glyceride, sorbitan fatty acid ester, sucrose fatty acid ester, surfactant, etc. can be used. These antifogging agents may be mixed with a resin in advance before use, or may be formed into various films and then coated on the surface.

[0046] As the colorant, for example, dyes such as anthraquinone compounds can be used for the purpose of adjusting the yellowness, and organic or inorganic pigments such as titanium oxide, talc, carbon black, etc. can be used for the purpose of imparting light-shielding properties.

[0047] The amount of the additives added is preferably in the range of 0.01 to 10% by mass based on the total mass of the block copolymer resin (I). By setting the content of the additives in the range of 0.01 to 10% by mass, various physical properties such as antioxidant performance, weather resistance, and lubricity can be well balanced, and the transparency, heat shrinkability, strength, etc. of the heat shrinkable multilayer film can be easily prevented from decreasing. The content of the additives is more preferably 0.05 to 5% by mass, and even more preferably 0.1 to 3% by mass.

[0048] Examples of the blocking inhibitor include organic fillers such as high impact polystyrene (HIPS), at least one crosslinked bead selected from the group consisting of vinyl aromatic hydrocarbon-(meth)acrylic acid esters, and (meth)acrylic acid copolymers, crosslinked beads of vinyl aromatic hydrocarbon copolymers, silica beads, quartz beads, etc. In order to obtain good transparency, it is preferable to use at least one crosslinked bead selected from the group consisting of HIPS, vinyl aromatic hydrocarbon-(meth)acrylic acid esters, and (meth)acrylic acid copolymers, crosslinked beads of vinyl aromatic hydrocarbon copolymers. The content of the blocking inhibitor is preferably 0.01 to 10% by mass, more preferably 0.1 to 5% by mass, based on the total mass of the block copolymer resin (I).

[0049] (Physical requirements) The block copolymer resin (I) according to the present invention contains a vinyl aromatic hydrocarbon monomer unit (X i ) and conjugated diene monomer units (Y i ) and is a block copolymer resin that satisfies the following (i-1) to (i-4). (i-1) The vinyl aromatic hydrocarbon monomer unit (X i ) and the conjugated diene monomer unit (Y i ) and the total (100 mass%) of the vinyl aromatic hydrocarbon monomer units (X i ) is 60% by mass or more and 82% by mass or less, and the conjugated diene monomer unit (Y i ) is 18 mass % or more and 40 mass % or less. (i-2) Weight average molecular weight (Mw i ) is between 100,000 and 300,000. (i-3) In dynamic viscoelasticity measurement, the loss tangent (tanδ) value was measured at a heating rate of 4°C / min, a frequency of 1Hz, and in the temperature range from room temperature to 130°C. i ) has at least one maximum value in the temperature range, and the loss tangent value (tan δ i ) is the maximum temperature T i (℃) is in the temperature range of 90℃ or more and 120℃ or less. (i-4) The vinyl aromatic hydrocarbon monomer unit (X i ) as the main component, and the conjugated diene monomer unit (Y i The soft phase, which is mainly composed of cellulose acetate, has a microphase separation structure with a lamellar structure.

[0050] When a shrink label is attached to a packaged object using the sleeve method (a method in which a cylindrical heat-shrinkable multilayer film is placed over the packaged object and then shrink-attached), if the label expands in the MD direction, shrink wrinkles are likely to occur, and if excessive shrinkage occurs, the film edge becomes arched, which can easily damage the appearance. Furthermore, if rapid shrinkage occurs in the TD direction near the temperature at which shrinkage begins, shrink wrinkles are likely to occur due to temperature unevenness. Therefore, in order to achieve good heat shrink finish, it is preferable that the dimensional change in the MD direction is small in the temperature range at the time of attachment, and that the heat shrinkage in the TD direction is gradual.

[0051] The heat-shrinkable multilayer film of the present invention contains a block copolymer resin (I) in at least one surface layer, and the block copolymer resin (I) satisfies the requirements (i-1) to (i-4) above, thereby imparting good shrinkage properties. That is, in the temperature range of 70 to 100°C, which is the shrink temperature when the heat-shrinkable multilayer film is attached to a beverage container as a shrink label, the film is imparted with a shrinkage property in which the dimensional change in the MD direction is small and the film slowly shrinks in the TD direction. As a result, when the heat-shrinkable multilayer film of the present invention is used as, for example, a shrink label, poor appearance due to wrinkles and the like is unlikely to occur, and good heat-shrink finish can be achieved. In this specification, the "MD direction" of the heat-shrinkable multilayer film means the direction along the resin flow in a continuous film production process. In addition, the "TD" direction means the direction perpendicular to the direction along the flow on the film.

[0052] Furthermore, by satisfying the above (i-1) to (i-4), the heat-shrinkable multilayer film of the present invention is less likely to whiten due to chemical attack by organic solvents contained in the printing ink during shrink label printing, and the solvent resistance is also improved. This is presumably because the molecular chain orientation of the block copolymer is reduced, which suppresses the generation of cracks due to organic solvents and thus suppresses whitening of the film. Furthermore, the block copolymer resin (I) according to this embodiment satisfies the solvent resistance required for practical use, such as excellent film elongation and resistance to breakage even after printing. Below, (i-1) to (i-4) will be described in detail.

[0053] (i-1) In the block copolymer resin (I) according to the present invention, the vinyl aromatic hydrocarbon monomer unit (X i ) and the conjugated diene monomer unit (Y i ) relative to the total (100 mass%) of the vinyl aromatic hydrocarbon monomer units (X i The mass proportion of the conjugated diene monomer unit (Y i The mass proportion of the vinyl aromatic hydrocarbon monomer unit (X) is 18% by mass or more and 40% by mass or less, preferably 20% by mass or more and 34% by mass or less, and more preferably 21% by mass or more and 30% by mass or less. i ) and the conjugated diene monomer unit (Y i When the mass ratio of the component (I) satisfies the above range, the balance between rigidity and elongation is good, and a microphase-separated structure having a lamellar structure is easily formed, which is preferable.

[0054] The vinyl aromatic hydrocarbon monomer unit (X) contained in the block copolymer resin (I) i ) and the conjugated diene monomer unit (Y i If the block copolymer resin (I) is produced by anionic polymerization, the mass ratio of the monomer units (Y iThe mass proportion of can be measured using a known halogen addition method.

[0055] A general procedure for measuring the mass proportion of conjugated diene monomer units by the halogen addition method is described below. A precisely weighed sample is dissolved in an organic solvent capable of completely dissolving the sample to obtain a test solution, and then an excess amount of iodine monochloride / carbon tetrachloride solution is added to the test solution to cause a sufficient reaction. Thereafter, the amount of unreacted iodine monochloride remaining in the solution is back-titrated with a sodium thiosulfate / ethanol solution to measure the amount of double bonds in the sample, and the amount of monomer units (Y i ) is calculated. In general, the ratio of the conjugated diene monomer units (Y i ) is calculated by the halogen addition method, and the rest is calculated as vinyl aromatic hydrocarbon monomer units (X i ) is preferably used as the mass ratio.

[0056] The conjugated diene monomer units (Y i By setting the mass ratio of the conjugated diene monomer unit (Y) within the above range, the heat-shrinkable multilayer film has a good balance between strength and rigidity. In addition, a microphase separation structure having a lamellar structure is easily obtained, and when the heat-shrinkable multilayer film is produced, the heat-shrinkable finish and the solvent resistance are good. i If the mass ratio of the conjugated diene monomer units (Y) is less than 18 mass%, the strength of the film decreases and the film becomes brittle. In addition, when the film is made into a heat-shrinkable multilayer film, it becomes difficult to obtain a microphase-separated structure having a lamellar structure. i If the mass ratio of the shrink label exceeds 40 mass %, the rigidity of the heat-shrinkable multilayer film will be too low, making it difficult to stretch the film. In addition, when the shrink label is attached to the packaged item using the sleeve method, the film will bend under the load (the shrink label's own weight), making it prone to poor attachment to the packaged item.

[0057] (i-2) In the block copolymer resin (I) according to the present invention, the weight average molecular weight (Mw i) is 100,000 or more and 300,000 or less, more preferably 100,000 or more and 2500,000 or less. i If the Mw is less than 100,000, the fluidity becomes too high when the film is extruded, which makes the film prone to have non-uniform width and thickness, and also tends to reduce the mechanical strength. i If the molecular weight exceeds 300,000, the fluidity is too low, and the temperature of the block copolymer resin (I) increases with the generation of excessive shear stress, which makes the block copolymer resin (I) more likely to deteriorate. The range of the fluidity of the block copolymer resin (I) is preferably 1 g / 10 min or more and 30 g / 10 min or less, more preferably 5 g / 10 min or more and 15 g / 10 min or less, in terms of the melt mass flow rate (MFR) measured at 200° C. under a load of 5 kg according to the measurement method described in ISO 1133.

[0058] Mw i is a value obtained as a polystyrene-equivalent molecular weight measured by a differential refractive index (RI) detector using gel permeation chromatography (GPC) with a general column. The polystyrene-equivalent molecular weight can be calculated from the molecular weight distribution of the block copolymer resin (I) obtained by preparing a calibration curve from the relationship between the molecular weight and the time required for detection using standard polystyrenes of known molecular weights.

[0059] (i-3) In the block copolymer resin (I) according to the present invention, the loss tangent (tanδ) measured in dynamic viscoelasticity measurement was measured at a temperature rise rate of 4° C. / min, a frequency of 1 Hz, and in a temperature range of room temperature to 130° C. i ) has at least one maximum value in the temperature range, and the loss tangent value (tan δ i ) is the maximum temperature T i (℃) is in the temperature range of 90℃ to 120℃. As mentioned above, the loss tangent value (tanδ i ) has at least one maximum value in the temperature range from room temperature to 130°C, and T iWhen the temperature is in the range of 90° C. or more and 120° C. or less, the heat-shrinkable multilayer film is given shrinkage characteristics that cause the film to shrink slowly in the TD direction, making it less likely to wrinkle during heat shrinkage.

[0060] The loss tangent value (tan δ) obtained by dynamic viscoelasticity measurement of block copolymer resin (I) i The temperature at which the temperature at which the coefficient of elasticity (T) is maximized can be determined by measuring the dynamic viscoelasticity of the block copolymer resin (I) at a temperature rise rate of 4°C / min and a frequency of 1 Hz in the temperature range from room temperature to 130°C using a dynamic viscoelasticity measuring device capable of applying a displacement at a constant frequency.

[0061] (i-4) In the block copolymer resin (I) according to the present invention, the vinyl aromatic hydrocarbon monomer unit (X i ) as the main component, and the conjugated diene monomer unit (Y i The soft phase, which is mainly composed of "vinyl aromatic hydrocarbon monomer units (X )", has a lamellar microphase separation structure. In the lamellar microphase separation structure, both the hard phase and the soft phase form a continuous phase, so that the strength of the film is good and the film is less likely to crack due to chemical attack by ink solvent. As a result, the solvent resistance is good. i The term "mainly composed of vinyl aromatic hydrocarbon monomer units (X )" means that the hard phase contains 60% by mass or more, preferably 80% by mass or more of vinyl aromatic hydrocarbon monomer units (X i Similarly, "conjugated diene monomer units (Y i The term "mainly composed of conjugated diene monomer units (Y i ) is included. The microphase separation structure of the lamellar structure is a structure of "monomer units (X i ) as the main component" and "monomer unit (Y iThe hard phase and the soft phase are likely to be formed when the ratio of the vinyl aromatic hydrocarbon to the soft phase is close to 50:50. The hard phase and the soft phase can be formed by adjusting the amount of monomer used in the polymerization reaction, or by adding any amount of monomer at once. That is, since the consumption rate of conjugated dienes (e.g. butadiene) is faster than that of vinyl aromatic hydrocarbons (e.g. styrene), when any amount of vinyl aromatic hydrocarbon and conjugated diene are added at once, the conjugated diene reacts mainly in the early stage to form the soft phase, and as the polymerization proceeds, the ratio of vinyl aromatic hydrocarbon gradually increases, and the hard phase is formed.

[0062] The presence or absence and state of the microphase separation structure in the block copolymer resin (I) can be visually confirmed by observing the heat-shrinkable multilayer film using, for example, a transmission electron microscope (TEM). Specifically, it can be confirmed by staining the unsaturated bonds in the conjugated diene with osmium tetroxide. At this time, the soft phase is stained darkly, and the hard phase is stained lightly, and is visually observed. The lamellar structure is a structure in which the soft phase (parts stained darkly) and the hard phase (parts stained lightly) are observed to form a continuous layer structure. Examples of structures other than the "lamellar structure" formed by the soft phase and the hard phase include a "sphere structure (also called a sea-island structure)" in which independent island-like soft phases exist in a fully continuous hard phase (i.e., a sea-like hard phase), and a "cylinder structure" in which a cylindrical soft phase exists in a fully continuous hard phase.

[0063] (Block copolymer resin (II)) The heat-shrinkable multilayer film according to an embodiment of the present invention comprises a block copolymer resin (I) and a vinyl aromatic hydrocarbon monomer unit (X ii ) and conjugated diene monomer units (Y ii It is preferable that the block copolymer resin (II) contains the following (ii-1) to (ii-3): (ii-1) The vinyl aromatic hydrocarbon monomer unit (X ii ) and the conjugated diene monomer unit (Yii ) relative to the total (100 mass%) of the vinyl aromatic hydrocarbon monomer units (X ii ) is 70% by mass or more and 84% by mass or less, and the conjugated diene monomer unit (Y ii ) is 16 mass % or more and 30 mass % or less. (ii-2) Weight average molecular weight (Mw ii ) is between 100,000 and 300,000. (ii-3) In dynamic viscoelasticity measurement, the loss tangent (tanδ) value measured at a heating rate of 4°C / min, a frequency of 1Hz, and a temperature range of room temperature to 130°C ii ) has at least one maximum value in the temperature range, and the loss tangent value (tan δ ii ) is the maximum temperature T ii (℃) is T i In relation to (°C), the following formulas (1) and (2) are satisfied. T i >T ii (1) 15≦(T i -T ii )≦35 (2)

[0064] The heat-shrinkable multilayer film of the present embodiment contains block copolymer resin (II) in at least one layer other than the surface layer containing the block copolymer resin (I), and thus has sufficient heat shrinkability that does not cause sagging due to insufficient shrinkage, and also tends to have better resistance to natural shrinkage. The layer containing the block copolymer resin (II) may be composed of two or more layers, but from the viewpoint of productivity, the layer containing the block copolymer resin (II) is preferably composed of one layer.

[0065] The block copolymer resin (II) is a vinyl aromatic hydrocarbon monomer unit (X ii ) and conjugated diene monomer units (Y iiThe block copolymer resin (II) according to the present embodiment is obtained by polymerizing a monomer containing a vinyl aromatic hydrocarbon and a conjugated diene, and is preferably obtained by polymerizing a vinyl aromatic hydrocarbon and a conjugated diene. In one embodiment of the present invention, the microphase-separated structure of the block copolymer resin (II) is preferably a structure other than a lamellar structure.

[0066] The vinyl aromatic hydrocarbon monomer unit (X) for constructing the block copolymer resin (II) ii ) and conjugated diene monomer units (Y ii ) may be the same monomer units as those constituting the block copolymer resin (I), and preferred examples are also the same. The method for producing the block copolymer resin (II) may be the same as that for the block copolymer resin (I), and it is preferable that the block copolymer resin (II) is obtained by anionic polymerization of a vinyl aromatic hydrocarbon and a conjugated diene. Therefore, the types and addition ratios of the organic solvent, polymerization initiator, randomizer, coupling agent, and polymerization terminator that can be used in the production may be the same as those used in the block copolymer resin (I), and there is no particular restriction on the order or ratio of adding these main raw materials and auxiliary raw materials. The microphase separation structure of the block copolymer resin (II) is not particularly limited, but is preferably not a lamellar structure, i.e., a spherical structure (island-in-the-sea structure) or a cylindrical structure. As a method for preventing the formation of a lamellar structure, for example, a method of adjusting the amount of monomers used in the polymerization reaction so that the ratio of the hard phase is higher than that of the soft phase, etc. can be mentioned.

[0067] Block copolymer resin (II) can be made into a composition by adding block copolymer resin (I), the above-mentioned other resins, and various additives, i.e., antioxidants (thermal stabilizers), ultraviolet absorbers (weather resistance agents), lubricants, plasticizers, antistatic agents, antifogging agents, antiblocking agents, colorants, etc., in the same manner as in the case of block copolymer resin (I). In this specification, the above composition is also referred to as block copolymer resin (II).

[0068] The block copolymer resin (II) preferably used in the heat shrinkable multilayer film of the present invention can be completed in a linear structure as in the block copolymer resin (I), or can be made into a branched structure. In this embodiment, the block copolymer resin (II) preferably contains a block copolymer having a branched structure. When the block copolymer resin (II) contains a block copolymer having a branched structure, it becomes easier to obtain the effect of maintaining the film thickness precision and improving the film properties such as the heat shrinkage rate and the natural shrinkage resistance.

[0069] The block copolymer resin (II) according to the present invention contains a vinyl aromatic hydrocarbon monomer unit (X ii ) and conjugated diene monomer units (Y ii The block copolymer resin contains the above-mentioned (ii-1) to (ii-3) and satisfies the following (ii-1) to (ii-3). The following describes (ii-1) to (ii-3) in detail.

[0070] (ii-1) In the block copolymer resin (II) according to the present invention, the vinyl aromatic hydrocarbon monomer unit (X ii ) and the conjugated diene monomer unit (Y ii ) relative to the total (100 mass%) of the vinyl aromatic hydrocarbon monomer units (X ii The mass proportion of the conjugated diene monomer unit (Y ii The mass proportion of the vinyl aromatic hydrocarbon monomer unit (X) is 16 mass% or more and 30 mass% or less, and more preferably 19 mass% or more and 27 mass% or less. ii ) and the conjugated diene monomer unit (Y ii ) is preferably in the above range, since it is possible to achieve a good balance between the rigidity and elongation of the heat-shrinkable multilayer film.

[0071] (ii-2) In the block copolymer resin (II) according to the present invention, the weight average molecular weight (Mw ii) is 100,000 or more and 300,000 or less, more preferably 100,000 or more and 250,000 or less. As in (i-2) of the block copolymer resin (I), Mw ii By setting Mw within the above range, the film is easily formed into a uniform width and thickness when extruded, and the mechanical strength is also not easily reduced. ii Also, the above Mw i It can be calculated by the same measurement method as above.

[0072] (ii-3) In the block copolymer resin (II) according to the present invention, in the dynamic viscoelasticity measurement, the loss tangent value (tanδ) was measured at a heating rate of 4° C. / min, a frequency of 1 Hz, and in the temperature range of room temperature to 130° C. ii ) has at least one maximum value in the temperature range, and the loss tangent value (tan δ ii ) is the maximum temperature T ii (℃) is T i In relation to (°C), the following formulas (1) and (2) are satisfied. T i >T ii (1) 15≦(T i -T ii )≦35 (2) Furthermore, i -T ii ) is more preferably 18 or more and 30 or less. T i and T ii By satisfying the relationship of both formulas (1) and (2), the balance between the shrink finish and the heat shrinkability is improved. ii As a method for achieving this, for example, in the process of simultaneously adding a vinyl aromatic hydrocarbon and a conjugated diene in a certain ratio during the production of the block copolymer resin (II), the addition ratio of the vinyl aromatic hydrocarbon and the conjugated diene can be changed. ii is the tan δ i It can be calculated by the same measurement method as above.

[0073] [Method of manufacturing heat-shrinkable multilayer film] In one embodiment of the method for producing a heat-shrinkable multilayer film of the present invention, an unstretched multilayer film containing the block copolymer resin (I) in at least one surface layer is subjected to dynamic viscoelasticity measurement at a heating rate of 4° C. / min, a frequency of 1 Hz, and a temperature range of room temperature to 130° C., to measure the loss modulus (E″) of the block copolymer resin (I). i ) is the maximum temperature T ic For (T ic -25)℃ or higher (T ic and stretching the unstretched multilayer film in the MD direction at a ratio of 1.00 to 1.30 and in the TD direction at a ratio of 3.0 to 8.0 at a temperature range of 0.15°C or lower. Here, the loss modulus (E'') of the block copolymer resin (I) is i ) can be calculated using the same device and method as in the dynamic viscoelasticity measurement described above.

[0074] More specifically, a preferred method includes a step of plasticizing the block copolymer resin (I) and other resins with an extruder (plasticization step), and then laminating two or more layers by continuous multilayer extrusion using a known T-die method or the like so that the block copolymer resin (I) is contained in at least one surface layer to obtain an unstretched multilayer film (lamination step), followed by a step of stretching the film in the MD direction and the TD direction (sequential stretching step). The specifications of the T-die generally used in the T-die method are not particularly limited as long as they are specifications that do not easily cause stagnation or retention of the resin flow, but it is preferable to use a coat hanger type T-die. The material of the flow path surface of the T-die is not limited as long as it has good resin peelability and does not easily cause stagnation or retention of the resin. Hard chrome plating is generally used.

[0075] To explain the successive stretching step in more detail, the multilayer film obtained in the lamination step is continuously stretched in the MD direction using an apparatus having rolls with a rotational difference while being kept in a preferred temperature range, and then both ends of the multilayer film are clamped with clips and continuously stretched in the TD direction as well. In other words, a successive stretching step (successive stretching method) using a successive stretching apparatus having a longitudinal stretching machine and a transverse stretching machine is generally preferably employed. In the method for producing a heat-shrinkable multilayer film of the present invention, the preferred temperature range refers to the loss modulus (E'') of the block copolymer resin (I) measured in dynamic viscoelasticity measurement at a heating rate of 4°C / min, a frequency of 1 Hz, and in a temperature range of room temperature to 130°C. i ) is the maximum temperature T ic For (T ic -25)℃ or higher (T ic +15)℃ or lower. The temperature range is more preferably T ic For (T ic -20)℃ or higher (T ic +10)° C. or less. By stretching within such a temperature range, the balance between the thermal shrinkage rate and the natural shrinkage rate and the thickness precision tend to be improved. In the method for producing a heat-shrinkable multilayer film of the present invention, the stretching ratio in the MD direction of the multilayer film is 1.00 times or more and 1.30 times or less, preferably more than 1.00 times and 1.20 times or less. The stretching ratio in the TD direction is 3.0 times or more and 8.0 times or less, preferably 4.0 times or more and 6.0 times or less. By setting the stretching ratio in the above range, the heat shrinkage rate is likely to be good. In the successive stretching step using the roll and tenter, by setting the stretching ratios in the MD direction and the TD direction within the above range, a heat-shrinkable multilayer film having a good balance between heat shrinkability and heat shrink finish is likely to be obtained.

[0076] The thickness of the heat-shrinkable multilayer film of the present invention is not particularly limited as long as it has the effect of the present invention. For example, in the case of shrink labels used for packaging beverage containers such as PET bottles, a thickness of 40 to 50 μm can be used when considering general printing equipment, printing method, attachment method, etc. Depending on the method of using the heat-shrinkable multilayer film, it can be made even thinner, for example, in the range of 20 μm or more and less than 40 μm.

[0077] However, if the thickness of the heat-shrinkable multilayer film is not uniform, lumps, flares, etc. may occur on the roll on which the film is wound, which may impair the appearance of the film. Therefore, it is preferable to suppress the thickness variation in the TD direction to within the range of the average thickness ±10%, more preferably within the range of the average thickness ±5%. In order to make the thickness of the heat-shrinkable multilayer film uniform, for example, measures such as making the thickness of the unstretched film uniform by using an automatic T-die during extrusion, or making the film temperature distribution uniform during stretching can be mentioned.

[0078] <Evaluation of heat shrinkable multilayer films> The present invention aims to obtain a heat-shrinkable multilayer film having better solvent resistance and good heat-shrink finish than conventional films. Therefore, the heat-shrinkable multilayer film of the present invention must have excellent heat-shrinkage properties. In addition, the film must have the basic properties of a heat-shrinkable film, such as film strength, transparency, natural shrinkage resistance, and film rigidity. Although the present invention is an invention of a heat-shrinkable multilayer film, in the following description, for simplicity, it may be referred to as a "heat-shrinkable film" or simply as a "film".

[0079] (Film strength) The film strength is the strength required against the tension applied to the film, for example, during film production or when the film is wound into a roll. However, the tensile elongation at break value obtained by tensile measurement of the obtained film in the normal temperature range is an index of film strength, rather than the strength value itself. In most cases, a film production method using a sequential stretching method is industrially adopted, and in this case, the strength of the film in the MD direction is required. In one embodiment of the present invention, the tensile elongation at break of the film in the MD direction tensile measurement of the heat-shrinkable multilayer film is preferably 200% or more, more preferably 300% or more. If the tensile elongation at break is less than 200%, the film is more likely to break, which may cause problems in production.

[0080] (film transparency) When the heat-shrinkable multilayer film according to the present embodiment is used as a heat-shrinkable label by, for example, applying printing to the surface layer, the film transparency is preferably such that the haze value is 10% or less, which prevents the film from becoming cloudy and maintains the design of the heat-shrinkable label.

[0081] (Natural shrinkage resistance) In the heat-shrinkable multilayer film of the present invention, in order to prevent the film from unintentionally shrinking during storage or transportation, causing problems such as misalignment of printing, it is desirable that the natural shrinkage rate, which is an index of resistance to natural shrinkage, is as close to zero as possible. For practical purposes, the natural shrinkage rate is preferably in the range of 0% to 4%, and more preferably in the range of 0% to 2%. The natural shrinkage rate can be calculated by storing a film immediately after production in a thermo-hygrostat for a certain period of time, measuring a reference linear distance between two points determined on the film before and after storage, and dividing the shrinkage length occurring after storage by the length before storage. That is, the natural shrinkage rate can be calculated by the following formula (4), where the reference linear distance before storage is L1 and the reference linear distance after storage is L2. (L1-L2) / (L1) × 100 (4) The temperature and humidity in the thermo-hygrostat are generally set to the severe conditions expected in practical use. In one aspect of the present invention, the natural shrinkage rate after storage for 7 days in a thermo-hygrostat at 40° C. is preferably 2% or less. In the heat-shrinkable film produced by the successive stretching method using the roll and tenter, the stretch ratio is often set higher in the TD direction than in the MD direction, and the value is usually the natural shrinkage rate in the TD direction.

[0082] (Film stiffness) The heat-shrinkable multilayer film of the present invention is usually produced by the above-mentioned sequential stretching method. When this is used as a heat-shrinkable label for a beverage container, for example, a product name, a display name, etc. are generally printed on the surface of the heat-shrinkable multilayer film to form a heat-shrinkable label, and then the heat-shrinkable label is once processed into a cylindrical shape that is thicker than the circumference of the body of the beverage container and matches the shape of each container with the TD direction as the circumferential direction, and the cylindrical heat-shrinkable label is temporarily attached to the beverage container. The heat-shrinkable label is then heated and shrunk so that the label is in close contact with the shape of the beverage container composed of complex curved surfaces, and then used. If the film rigidity of the heat-shrinkable label before heat-shrinking is insufficient, problems may occur in the process of processing the heat-shrinkable label into a cylindrical shape, or when the cylindrical heat-shrinkable label is temporarily attached to the container, it is difficult to maintain the cylindrical shape until it is heat-shrunk. For this reason, for example, the end of the cylindrical film may be curved, or unnecessary wrinkles or waves may occur in the film before heat-shrinking, causing problems in the heat-shrinkable finish. Therefore, a heat shrinkable film needs to have a suitable film rigidity as a basic property. The film rigidity can be measured by the elastic modulus in the MD direction of the film tensile test. The tensile elastic modulus varies depending on the chemical composition of the block copolymer resin used in the film, and is preferably in the suitable range of 900 MPa to 2000 MPa, more preferably 950 MPa to 1500 MPa.

[0083] (Solvent resistance) The heat-shrinkable multilayer film of the present invention has improved solvent resistance compared to conventional films, and is less susceptible to erosion by organic solvents even after printing with ink containing organic solvents. Therefore, the film strength is less likely to decrease, and phenomena such as whitening and shrinkage are less likely to occur. The maximum ethyl acetate concentration at which whitening does not occur when a mixed solution of isopropyl alcohol and ethyl acetate is dropped onto the film is used as an index of the film's solvent resistance, and the higher this value, the better the solvent resistance.

[0084] (Heat shrink finish) The heat-shrinkable multilayer film of the present invention has improved solvent resistance and excellent heat shrink finish compared to conventional films. The smaller the dimensional change in the MD direction in the temperature range of 70°C to 100°C, the less likely wrinkles or poor appearance at the film ends will occur when packaging a packaged object having a complex shape. That is, in one aspect of the present invention, the maximum heat shrinkage rate in the MD direction in the temperature range of 70°C to 100°C is preferably 5% or less and the minimum value is -3% or more, and more preferably 3% or less and the minimum value is -2% or more.

[0085] Furthermore, if the heat shrinkage rate of the heat shrinkable label is low, a gap (slack) may occur between the packaged item and the label. Therefore, in one aspect of the present invention, it is preferable that the heat shrinkage rate of the heat shrinkable multilayer film in the TD direction at 80°C is 30% or more and the heat shrinkage rate at 100°C is 65% or more.

[0086] (Application) The heat-shrinkable multilayer film according to the embodiment of the present invention can be suitably used as a heat-shrinkable label as described above. The heat-shrinkable multilayer film according to the present invention can also be used for purposes other than the heat-shrinkable label, such as a heat-shrinkable cap seal, an overpack film, or various other packaging forms.

[0087] [Heat shrink labels] The heat-shrinkable label of the present invention includes the above-mentioned heat-shrinkable multilayer film. The heat-shrinkable label preferably has a configuration in which a printing layer is laminated on a surface layer containing the resin (I) of the heat-shrinkable multilayer film. A heat-shrinkable label comprising the heat-shrinkable multilayer film of the present invention adheres to surfaces without wrinkling even if the surface has a complex shape, and is less susceptible to the effects of organic solvents during printing, resulting in excellent design.

[0088] [Label manufacturing method] The label of the present invention refers to a label obtained by heat shrinking the heat shrinkable label. That is, one embodiment of the present invention is a method for producing a label by heat shrinking the heat shrinkable label. The label manufacturing method of the present invention is appropriately adjusted depending on the package to which the label is to be attached. For example, when the label is used for a beverage container such as a PET bottle, the heat-shrinkable label is preferably heat-shrunk at a temperature of 60° C. or more and 110° C. or less.

[0089] The label is preferably used for packaging containers. The label obtained from the heat-shrinkable multilayer film of the present invention can be used for, for example, metal containers (three-piece cans and two-piece cans, bottle cans with lids, etc.) made of tinplate, tin-free steel (TFS), aluminum, stainless steel, etc., glass containers, or plastic containers made of polyethylene terephthalate (PET), polyethylene, polypropylene, etc. The heat-shrinkable multilayer film of the present embodiment is excellent in heat shrink finish without wrinkles even when used as a shrink label for a packaged object having a complex shape. In addition, whitening is unlikely to occur due to chemical attack by organic solvents during printing, and film strength is easily maintained, so that the solvent resistance is improved compared to conventional methods. EXAMPLES

[0090] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The chemical composition and various physical properties of each block copolymer produced below are shown in Table 1. Tables 2 and 3 show the blending ratio, various physical properties, and evaluation results of the block copolymer resins used in each Example and Comparative Example. In addition, the columns "Surface layer" and "Intermediate layer" in Tables 2 to 3 show the type of block copolymer resin used in each layer (see the column "Type of block copolymer resin" in Tables 2 to 3). That is, when the block copolymer resin used in each Example and Comparative Example satisfies the constitution of block copolymer resin (I) of the present invention, "(I)" is entered in the column of type of block copolymer resin, and when it satisfies the constitution of block copolymer resin (II), "(II)" is entered. When it does not fall into either block copolymer resin (I) or (II), "(-)" is entered.

[0091] <Production of block copolymer> In order to demonstrate the effect of the heat-shrinkable multilayer film of the present invention, block copolymers (A) to (H) of Reference Examples 1 to 8 were prepared as examples for constituting block copolymer resin (I) and block copolymer resin (II). The procedures are as follows.

[0092] (Reference Example 1) Production of Block Copolymer (A) (1) 1m 3 The reaction vessel was charged with 467 kg of cyclohexane and 70.1 g of tetrahydrofuran, and 1260 mL of n-butyllithium (10 mass % cyclohexane solution) was added thereto while stirring at an internal temperature of 30°C. (2) At an internal temperature of 30°C, 82.2 kg of styrene was added and the temperature was raised to polymerize. The internal temperature rose to 67°C. (3) At an internal temperature of 45°C, 4170 mL of n-butyllithium (10% by mass solution in cyclohexane) was added, followed by the addition of 69.8 kg of styrene, and the temperature was raised to polymerize. The internal temperature rose to 75°C. (4) At an internal temperature of 50°C, 48.0 kg of butadiene was added, and the temperature was raised to polymerize. The internal temperature rose to 81°C. (5) At an internal temperature of 75° C., 600 g of epoxidized soybean oil was added, and the mixture was stirred at 75° C. for 10 minutes to complete the polymerization. (6) 300 g of water was added to inactivate all of the polymerization active terminals, thereby obtaining a polymerization liquid containing a block copolymer (A). (7) This polymerization liquid was melt-pelletized in a degassing extruder to obtain a block copolymer (A).

[0093] (Reference Example 2) Production of Block Copolymer (B) (1) 1m 3 The reaction vessel was charged with 500 kg of cyclohexane and 75 g of tetrahydrofuran, and 1320 mL of n-butyllithium (10 mass % cyclohexane solution) was added thereto with stirring at an internal temperature of 30°C. (2) At an internal temperature of 30°C, 15.6 kg of styrene was added and the temperature was raised to polymerize. The internal temperature rose to 52°C. (3) At an internal temperature of 50°C, 65.2 kg of styrene and 48.0 kg of butadiene were added, and the temperature was raised to polymerize. The internal temperature rose to 104°C. (4) At an internal temperature of 60°C, 9.0 g of water was added and reacted sufficiently, after which 71.2 kg of styrene was added and the temperature was raised to complete the polymerization. The internal temperature rose to 87°C. (5) 300 g of water was added to inactivate all of the polymerization active terminals, thereby obtaining a polymerization liquid containing a block copolymer (B). (6) This polymerization liquid was melt-pelletized in a degassing extruder to obtain a block copolymer (B).

[0094] (Reference Example 3) Production of Block Copolymer (C) (1) 1m 3 The reaction vessel was charged with 467 kg of cyclohexane and 70.1 g of tetrahydrofuran, and 1390 mL of n-butyllithium (10 mass % cyclohexane solution) was added thereto while stirring at an internal temperature of 30°C. (2) At an internal temperature of 30°C, 93.8 kg of styrene was added and the temperature was raised to polymerize. The internal temperature rose to 73°C. (3) At an internal temperature of 45°C, 3800 mL of n-butyllithium (10% by mass solution in cyclohexane) was added, and then 42.2 kg of styrene was added and polymerized by increasing the temperature. The internal temperature rose to 66°C. (4) While maintaining the internal temperature at 80°C, a total of 8.0 kg of styrene and a total of 2.0 kg of butadiene were added simultaneously at constant addition rates of 48.0 kg / h and 12.0 kg / h, respectively, and the internal temperature was maintained at 80°C for 10 minutes after completion of the addition. (5) At an internal temperature of 50°C, 50.0 kg of butadiene was added, and the temperature was raised to polymerize. The internal temperature rose to 82°C. (6) At an internal temperature of 60°C, 4.0 kg of styrene was added, and the internal temperature was raised to 75°C to carry out polymerization. (7) At an internal temperature of 75°C, 570 g of epoxidized soybean oil was added, and the mixture was stirred at 75°C for 10 minutes to complete the polymerization. (8) 300 g of water was added to inactivate all of the polymerization active terminals, and a polymerization liquid containing a block copolymer (C) was obtained. (9) This polymerization liquid was melt-pelletized in a degassing extruder to obtain a block copolymer (C).

[0095] (Reference Example 4) Production of Block Copolymer (D) (1) 1m 3 The reaction vessel was charged with 490 kg of cyclohexane and 73.5 g of tetrahydrofuran, and 960 mL of n-butyllithium (10 mass % cyclohexane solution) was added thereto while stirring at an internal temperature of 30°C. (2) At an internal temperature of 30°C, 105.0 kg of styrene was added and the temperature was raised to polymerize. The internal temperature rose to 83°C. (3) At an internal temperature of 55°C, 1260 mL of n-butyllithium (10% by mass solution in cyclohexane) was added, and then 23.1 kg of styrene was added and polymerized by increasing the temperature. The internal temperature rose to 62°C. (4) At an internal temperature of 45°C, 48.3 kg of styrene and 33.6 kg of butadiene were added, and the polymerization was completed by increasing the temperature. The internal temperature rose to 88°C. (5) 300 g of water was added to inactivate all of the polymerization active terminals, thereby obtaining a polymerization liquid containing a block copolymer (D). (6) This polymerization liquid was melt-pelletized in a degassing extruder to obtain a block copolymer (D).

[0096] (Reference Example 5) Production of block copolymer (E) (1) 1m 3 The reaction vessel was charged with 490 kg of cyclohexane and 73.5 g of tetrahydrofuran, and 1650 mL of n-butyllithium (10 mass % cyclohexane solution) was added thereto while stirring at an internal temperature of 30°C. (2) At an internal temperature of 30°C, 35.7 kg of styrene was added and the temperature was raised to polymerize. The internal temperature rose to 55°C. (3) At an internal temperature of 40°C, 69.3 kg of styrene and 8.9 kg of butadiene were added, and the temperature was raised to polymerize. The internal temperature rose to 73°C. (4) At an internal temperature of 60°C, 5.5 g of water was added and allowed to react sufficiently, after which 69.3 kg of styrene and 26.8 kg of butadiene were added and the temperature was raised to complete the polymerization. The internal temperature rose to 105°C. (5) 300 g of water was added to inactivate all of the polymerization active terminals, thereby obtaining a polymerization liquid containing a block copolymer (E). (6) This polymerization liquid was melt-pelletized in a degassing extruder to obtain a block copolymer (E).

[0097] (Reference Example 6) Production of block copolymer (F) (1) 1m 3 The reaction vessel was charged with 500 kg of cyclohexane and 75 g of tetrahydrofuran, and 2000 mL of n-butyllithium (10 mass % cyclohexane solution) was added thereto while stirring at an internal temperature of 30°C. (2) At an internal temperature of 30°C, 4.0 kg of styrene was added and the temperature was raised to polymerize. The internal temperature rose to 35°C. (3) While maintaining the internal temperature at 80°C, a total of 144.0 kg of styrene and a total of 12.0 kg of butadiene were added simultaneously at constant addition rates of 144.0 kg / h and 12.0 kg / h, respectively, and the internal temperature was maintained at 80°C for 10 minutes after completion of the addition. (4) At an internal temperature of 60°C, 36.0 kg of butadiene was added, and the temperature was raised to polymerize. The internal temperature rose to 86°C. (5) At an internal temperature of 70°C, 4.0 kg of styrene was added, and the temperature was raised to complete the polymerization. The internal temperature rose to 73°C. (6) 300 g of water was added to inactivate all of the polymerization active terminals, and a polymerization liquid containing a block copolymer (F) was obtained. (7) This polymerization liquid was melt-pelletized in a degassing extruder to obtain a block copolymer (F).

[0098] (Reference Example 7) Production of block copolymer (G) (1) 1m 3 The reaction vessel was charged with 500 kg of cyclohexane and 75 g of tetrahydrofuran, and 2000 mL of n-butyllithium (10 mass % cyclohexane solution) was added thereto while stirring at an internal temperature of 30°C. (2) At an internal temperature of 30°C, 4.0 kg of styrene was added and the temperature was raised to polymerize. The internal temperature rose to 35°C. (3) While maintaining the internal temperature at 80°C, a total of 144.0 kg of styrene and a total of 12.0 kg of butadiene were added simultaneously at constant addition rates of 144.0 kg / h and 12.0 kg / h, respectively, and the internal temperature was maintained at 80°C for 10 minutes after completion of the addition. (4) At an internal temperature of 60°C, 36.0 kg of butadiene was added, and the temperature was raised to polymerize. The internal temperature rose to 86°C. (5) At an internal temperature of 70°C, 4.0 kg of styrene was added and the temperature was raised to polymerize. The internal temperature rose to 73°C. (6) At an internal temperature of 75°C, 190 g of epoxidized soybean oil was added, and the mixture was stirred at 75°C for 10 minutes to complete the polymerization. (6) 300 g of water was added to inactivate all of the polymerization active terminals, thereby obtaining a polymerization liquid containing a block copolymer (G). (7) This polymerization liquid was melt-pelletized in a degassing extruder to obtain a block copolymer (G).

[0099] (Reference Example 8) Production of Block Copolymer (H) (1) 1m 3The reaction vessel was charged with 500 kg of cyclohexane and 75 g of tetrahydrofuran, and 2000 mL of n-butyllithium (10 mass % cyclohexane solution) was added thereto while stirring at an internal temperature of 30°C. (2) At an internal temperature of 30°C, 4.0 kg of styrene was added and the temperature was raised to polymerize. The internal temperature rose to 35°C. (3) While maintaining the internal temperature at 80°C, a total of 144.0 kg of styrene and a total of 21.0 kg of butadiene were added simultaneously at constant addition rates of 144.0 kg / h and 21.0 kg / h, respectively, and the internal temperature was maintained at 80°C for 10 minutes after completion of the addition. (4) At an internal temperature of 60°C, 27.0 kg of butadiene was added, and the temperature was raised to polymerize. The internal temperature rose to 76°C. (5) At an internal temperature of 70°C, 4.0 kg of styrene was added, and the temperature was raised to complete the polymerization. The internal temperature rose to 73°C. (6) 300 g of water was added to inactivate all of the polymerization active terminals, and a polymerization liquid containing a block copolymer (H) was obtained. (7) This polymerization liquid was melt-pelletized in a degassing extruder to obtain a block copolymer (H).

[0100] The polystyrene resin in the table was manufactured by Toyo Styrene Co., Ltd. and has the trade name G200C.

[0101] Example 1: Preparation of heat-shrinkable multilayer film As the raw material of the block copolymer resin (I), pellets of the block copolymer (A) of Reference Example 1 were prepared. As the raw material of the block copolymer resin (II), pellets of the block copolymer (F) of Reference Example 6 and the block copolymer (G) of Reference Example 7 were dry-mixed in a mass ratio of 67:33 to prepare mixed pellets. Each pellet was fed to a multilayer sheet film-forming machine so that the block copolymer resin (I) was laminated on both surfaces of the block copolymer resin (II), and a sheet having a total thickness of 300 μm and a thickness ratio of the surface layer / intermediate layer / surface layer of 10 / 80 / 10 was extrusion-molded. The sheet that left the multilayer sheet film-forming machine was immediately sent to the longitudinal stretching machine of the sequential stretching device, and stretched 1.05 times in the MD direction at 70 ° C. and 4.5 times in the TD direction at 95 ° C. to obtain the heat-shrinkable multilayer film of Example 1. The stretching temperature and stretching conditions for the obtained heat-shrinkable multilayer film are also shown in Table 2.

[0102] (Examples 2 to 6, Comparative Examples 1 to 4) The heat-shrinkable multilayer films of each example were obtained in the same manner as in Example 1, except that the blending amounts of block copolymer resin (I) and block copolymer resin (II) and the production conditions were as shown in Tables 2 and 3.

[0103] <Evaluation of physical properties> The methods for evaluating the physical properties of the block copolymer resin (I) and block copolymer resin (II) used in the heat-shrinkable multilayer films of Examples 1 to 6 and Comparative Examples 1 to 4, that is, the measurement of the mass ratio of the vinyl aromatic hydrocarbon monomer unit and the mass ratio of the conjugated diene monomer unit contained in the block copolymer resins (I) and (II), the measurement of the weight average molecular weight, the measurement of the dynamic viscoelasticity, the observation of the microphase separation structure, and the observation of the presence or absence of a branched structure, are described below. Except for the case where the resin pellets of the Reference Examples can be used as they are as evaluation samples, the resin physical properties of the block copolymer resin (I) and block copolymer resin (II) used in each heat-shrinkable multilayer film of the Examples and Comparative Examples were evaluated using new pellet samples prepared by the following method, rather than dry-mixed pellets. That is, according to the blending ratios of the Examples and Comparative Examples shown in Tables 2 to 3, pellets of the block copolymer and polystyrene resin of each Reference Example were dry-mixed to prepare a pellet mixture, and the pellet mixture was melt-kneaded at 210°C using an extruder to prepare pellets, which were then used for evaluation. In this specification, these may be referred to as, for example, "a pellet sample of block copolymer resin (I) of Example 3." Also, a "pellet sample of block copolymer resin (I) of Example 1" and a "pellet sample of block copolymer (A) of Reference Example 1" are the same thing.

[0104] <Measurement of mass ratio of vinyl aromatic hydrocarbon monomer unit> The mass proportion of the vinyl aromatic hydrocarbon monomer unit contained in the block copolymer resin (I) and the block copolymer resin (II) in each Example and Comparative Example was determined by subtracting the measured mass proportion (mass%) of the conjugated diene monomer unit from the total (100 mass%). The results are shown in Tables 1 to 3.

[0105] <Measurement of mass ratio of conjugated diene monomer units> The mass ratio of the conjugated diene monomer unit contained in the block copolymer resin (I) and the block copolymer resin (II) of each Example and Comparative Example was measured using a pellet sample of the block copolymer resin (I) and a pellet sample of the block copolymer resin (II) of each Example and Comparative Example according to the procedures (1) to (6) shown below. The results are shown in Tables 1 to 3. (1) 0.1 g of a sample was dissolved in 50 mL of chloroform. (2) 25 mL of iodine monochloride / carbon tetrachloride solution was added and mixed thoroughly, and then the mixture was left in the dark for 1 hour. (3) 75 mL of 2.5% potassium iodide solution was added and mixed thoroughly. (4) A 20% sodium thiosulfate / ethanol solution was added with sufficient stirring until the liquid turned pale yellow. (5) Approximately 0.5 mL of 1% starch indicator was added, and the solution was titrated again with 20% sodium thiosulfate / ethanol solution until it became colorless. (6) After the titration was completed, the amount of sodium thiosulfate / ethanol solution consumed, a [mL], was measured. To perform a blank measurement correction, the steps (1) to (6) were also performed on chloroform alone, and the amount of sodium thiosulfate / ethanol solution consumed b [mL] was measured. The conjugated diene content was calculated from the measured values ​​according to the following formula. Conjugated diene content (%) = [(ba) x 0.1 x c x 27 / 1000] / W x 100 c: Potency of 20% sodium thiosulfate / ethanol solution W: Sample weight [g]

[0106] <Method for measuring weight average molecular weight> The weight average molecular weight Mw of the block copolymer resin (I) and the block copolymer resin (II) in each of the examples and comparative examples i , Mw ii The measurements were performed using pellet samples of block copolymer resin (I) and pellet samples of block copolymer resin (II) of each Example and Comparative Example, using the following device. The results are shown in Tables 1 to 3. Device name: High-speed GPC device HLC-8220 (manufactured by Tosoh Corporation) Column: 3 PL gel MIXED-B in series Temperature: 40℃ Detection: Differential refractive index Solvent (eluent): Tetrahydrofuran Concentration: 2wt% A calibration curve was prepared using standard polystyrene (Polymer Laboratories), and the weight average molecular weight was calculated as the molecular weight converted into polystyrene.

[0107] <Measurement of loss tangent and loss modulus> Dynamic viscoelasticity measurements of the block copolymer resin (I) and block copolymer resin (II) of each Example and Comparative Example were carried out using pellet samples of the block copolymer resin (I) and pellet samples of the block copolymer resin (II) of each Example and Comparative Example according to the procedures shown in (1) and (2) below, and the loss tangent value (tanδ) of the block copolymer resin (I) versus temperature was measured. i ), loss modulus (E'' i ), and the loss tangent value (tanδ ii From the dynamic viscoelasticity curves obtained, the temperatures at which the maximum values ​​were observed, T i , T ii , T ic asked for. (1) Each pellet sample was hot-pressed at 200 to 250° C. to produce a sheet having a thickness of 0.1 to 0.5 mm. (2) A test piece measuring 25 mm x 5 mm was cut out from this sheet and stored in a room at 23°C and 50% RH for at least 24 hours for aging treatment. After that, the storage modulus and loss modulus were measured at the following heating rate and frequency in the following temperature range using the following equipment, and the loss tangent value was calculated. Equipment: TA Instruments solid viscoelasticity measuring device RSAIII Temperature range: Room temperature to 130℃ Set temperature rise rate: 4℃ / min Measurement frequency: 1Hz

[0108] <Observation of microphase separation structure> The microphase-separated structures of the block copolymer resin (I) and the block copolymer resin (II) in each of the Examples and Comparative Examples were measured by the following method using pellet samples of the block copolymer resin (I) and pellet samples of the block copolymer resin (II) in each of the Examples and Comparative Examples. Each resin pellet was embedded in epoxy resin, and a cross section of the heat shrinkable film before heat shrinkage was obtained using a microtome. The cross section was then observed with a transmission electron microscope (TEM) to visually observe the microphase separation structure in the heat shrinkable film before heat shrinkage. The results are shown in Tables 1 to 3.

[0109] <Branched structure> The presence or absence of branched structures in the block copolymer resins (I) and (II) in each of the Examples and Comparative Examples was confirmed by the presence or absence of multiple values ​​of the molecular weight peaks resulting from branched chains having 1 to 4 chains, based on the shape of the molecular weight distribution chart obtained by the GPC apparatus. The results are shown in Tables 1 to 3.

[0110] <Evaluation of film properties> The physical properties of the heat-shrinkable multilayer films of the respective Examples and Comparative Examples were measured according to the following methods. The results are shown in Tables 2-3.

[0111] <Film strength> (Measurement of tensile modulus and tensile elongation at break) In evaluating the film strength and rigidity in the MD direction required for the heat-shrinkable multilayer film of the present invention, the tensile elongation at break and tensile modulus, which serve as indicators thereof, were measured by the following methods and evaluated as film strength and film rigidity, respectively, according to the criteria described below. (1) A rectangular sample piece having a width of 100 mm in the MD direction and a width of 10 mm in the TD direction was cut out from the stretched film. (2) Using a Tensilon universal material testing machine manufactured by Orientec Co., Ltd., the cut-out sample pieces were subjected to tensile stress in the MD direction at a measurement temperature of 23°C and a tensile speed of 200 mm / min, and the tensile modulus was calculated from the stress-strain curve and the cross-sectional area of ​​the sample pieces. The tensile elongation at break was calculated based on the displacement at the time of film breakage. If the tensile elongation in the MD direction was 200% or more, it was determined that the film had sufficient strength, and if the tensile modulus in the MD direction was 900 MPa or more, it was determined that the film also had sufficient rigidity.

[0112] <Transparency> (HAZE value measurement) The haze value of the heat shrinkable multilayer film was measured by the following method to evaluate the transparency. The smaller the haze value, the more preferable it is, but a haze value of 10% or less was determined to be sufficient transparency for practical use. (1) A sample piece having a width of 50 mm in the MD direction and a width of 100 mm in the TD direction was cut out from the stretched film. (2) The haze value of the film was measured using a turbidity meter NDH2000 manufactured by Nippon Denshoku Industries Co., Ltd.

[0113] <Natural shrinkage resistance> The natural shrinkage in the TD direction was measured according to the following procedure. (1) A test piece measuring approximately 75 mm in the MD direction and approximately 400 mm in the TD direction was cut out from the stretched film. (2) Marked lines were marked at 300.0 mm intervals in the TD direction of this test piece. (3) The stretched film was stored in an environmental test chamber at 40°C. (4) After 7 days of storage, the film was taken out and the distance L (mm) between the marked lines was measured to the nearest 0.1 mm using a caliper. (5) The natural shrinkage rate was calculated using the following formula. Natural shrinkage rate (%) = {(300.0-L) / 300.0} x 100

[0114] The results of the film property evaluation for the items shown above show that the heat-shrinkable multilayer film of the present invention maintains various properties such as film strength, transparency, natural shrinkage resistance, film rigidity, etc. Furthermore, the evaluation results of the solvent resistance and heat shrink finish, which are one of the objects of the present invention, are described below.

[0115] <Evaluation of Solvent Resistance> Solvent resistance was measured by the following method and evaluated according to the criteria described below. (1) A sample piece measuring 300 mm in width in the MD direction and 300 mm in width in the TD direction was cut out and placed on a glass plate. (2) Five types of mixed solvents were prepared by varying the volumetric mixing ratio of 2-propanol / ethyl acetate from 30% to 50% in increments of 5%. 0.05 mL of each mixture was dropped onto the film using a dropper in an environment of 23°C and 50% humidity. (3) After the dropped mixed solution had completely evaporated and disappeared, the appearance of the film was visually confirmed, and the maximum concentration of ethyl acetate at which the film did not turn white was recorded as the measured value. When it was difficult to judge by visual inspection, the smaller value was used. A: No film whitening occurs, and the maximum concentration of ethyl acetate in 2-propanol / ethyl acetate is 45% by volume or more. B: No film whitening occurs, and the maximum concentration of ethyl acetate in 2-propanol / ethyl acetate is 35% by volume or more and less than 45% by volume. C: No film whitening occurs, and the maximum concentration of ethyl acetate in 2-propanol / ethyl acetate is less than 35% by volume. Of the above, a grade of B or higher was deemed to be acceptable (excellent solvent resistance).

[0116] <Guideline values ​​for heat shrink finish and actual evaluation results for heat shrink finish> As a guideline for heat shrinkage finish, the heat shrinkage measured in the MD direction at temperatures between 70°C and 100°C was obtained by the following procedures (1) to (4). Note that the MD direction may temporarily elongate, and in such a case, the shrinkage value (minimum value) was calculated as a negative value. The maximum and minimum values ​​of the heat shrinkage were compared with the actual heat shrinkage finish described below, that is, the validity of the tendency that wrinkles and appearance defects at the film edges in particular become less noticeable when a heat-shrinkable multilayer film having a maximum heat shrinkage of 5% or less and a minimum heat shrinkage of -3% or less is heat-shrunk was judged. (1) A test piece having a width of 100 mm in the MD direction and a width of 100 mm in the TD direction was cut out from the stretched film. (2) The test piece was completely immersed in 70°C warm water for 10 seconds, then taken out and immediately cooled in water. After cooling in water, the test piece was thoroughly wiped to remove moisture, and the length M (mm) in the MD direction was measured. (3) The thermal shrinkage rate in the MD direction at 70°C was calculated using the following formula, and the decimal point was rounded off to an integer value. Thermal shrinkage rate in MD direction (%) = {(100-M) / 100} x 100 (4) The measurements were repeated in the same manner as in (1) to (3) above, with the hot water temperature being increased by 5°C at a time up to 100°C. A shrinkage curve in the MD direction from 70°C to 100°C was created, the maximum and minimum values ​​were obtained, and the difference between them was calculated.

[0117] Next, the actual heat shrink finish of the heat shrinkable label was evaluated according to the following steps (1) to (4). (1) As a representative cylindrical container, a PET container (mouth diameter 20 mmφ, body diameter 68 mmφ, height 210 mm, AS ONE PET bottle 500 round, model number: M1-354-02) and a cylindrical heat-shrinkable label made from heat-shrinkable film with a height of 100 mm and a diameter of 74 mm (5 mm was used for the adhesive margin) were prepared. (2) The bottom end of the heat-shrinkable label was temporarily attached to the PET container with tape so that the top end of the film was positioned directly 15 mm above the point where the body of the PET bottle began to narrow toward the nozzle. (3) The PET bottle with the heat-shrinkable label temporarily attached was placed in a high-temperature bath set at 80° C. for 30 seconds, and then immediately removed from the high-temperature bath and allowed to cool to room temperature. (4) The state of heat shrinkage of the heat shrink label, especially the presence or absence of wrinkles at the upper end of the film, was observed. It goes without saying that it is preferable for the heat shrink label to shrink in a state of adhering to the PET bottle without slack or wrinkles, even in a three-dimensional curved surface. Films that were clearly wrinkled by visual inspection were given a "C" rating, as they had a tendency to wrinkle easily. On the other hand, those in which the adhesion of the heat shrink label appeared particularly good were given an "A" rating, and those in which the adhesion of the heat shrink label was good were given a "B" rating. Of these, those with a "B" rating or higher were considered to have passed. The results are shown in Tables 2 to 3.

[0118] (Measurement of thermal shrinkage in TD direction) The heat shrinkage in the TD direction was measured by the following methods (1) to (3). It is possible to simultaneously measure the heat shrinkage in the MD direction and the heat shrinkage in the TD direction at the same temperature. (1) A test piece having a width of 100 mm in the MD direction and a width of 100 mm in the TD direction was cut out from the stretched film. (2) The test piece was completely immersed in 80°C water for 10 seconds, then taken out and immediately cooled in water. After cooling in water, the test piece was thoroughly wiped to remove moisture, and the length L (mm) in the TD direction was measured. (3) The thermal shrinkage rate was calculated using the following formula, and the decimal point was rounded off to an integer value. Thermal shrinkage rate in TD direction (%) = {(100-L) / 100} x 100 (4) The heat shrinkage in the TD direction was also measured in the same manner as above when immersed in warm water at 100° C. Regarding the heat shrinkage in the TD direction, if the heat shrinkage in the TD direction at 80° C. is 30% or more and the heat shrinkage in the TD direction at 100° C. is 65% or more, it is judged to be a heat shrinkable film that exhibits good heat shrinkability and does not cause sagging due to insufficient shrinkage.

[0119] [Table 1]

[0120] [Table 2]

[0121] [Table 3]

[0122] The heat-shrinkable multilayer films of Examples 1 to 6 had good solvent resistance and heat-shrink finish, and also had a good balance of various physical properties such as film strength, transparency, resistance to natural shrinkage, and film rigidity. On the other hand, the heat shrinkable multilayer films of Comparative Examples 1 to 4 were inferior in either heat shrink finish or solvent resistance, and no film satisfying both of these performances was obtained. This shows that the heat shrinkable multilayer film of this embodiment is a material that maintains the various physical properties required of a shrink film, while being superior in heat shrink finish, which is the greatest feature of the present invention, and also has excellent solvent resistance to the diluting organic solvent of the ink. In addition, in the present invention, it has been shown that if the maximum value of the heat shrinkage rate in the MD direction at 70°C to 100°C is 5% or less and the minimum value is -3% or more, the finish when actually heat shrunk is also good. [Industrial Applicability]

[0123] The heat-shrinkable multilayer film of the present invention maintains various physical properties such as film strength, transparency, natural shrinkage resistance, and film rigidity, while having good solvent resistance, so that the film strength is not significantly reduced even when printing is performed. Furthermore, since the heat-shrinkable finish is better than that of conventional films, the film can be suitably used as a shrink film for shrink labels for various containers and the like, which require more appropriate printing and shape.

Claims

1. A heat shrinkable multilayer film having at least two layers, Vinyl aromatic hydrocarbon monomer units (X i ) and conjugated diene monomer units (Y i At least one surface layer of the heat-shrinkable multilayer film contains a block copolymer resin (I) containing A block copolymer resin (II) containing a vinyl aromatic hydrocarbon monomer unit (X ii ) and a conjugated diene monomer unit (Y ii ) is contained in at least one layer other than the surface layer containing the block copolymer resin (I), The heat-shrinkable multilayer film, wherein the block copolymer resin (I) satisfies the following (i-1) to (i-4), and the block copolymer resin (II) satisfies the following (ii-1) to (ii-3): (i-1) The vinyl aromatic hydrocarbon monomer unit (X i ) and the conjugated diene monomer unit (Y i ) and the total (100 mass%) of the vinyl aromatic hydrocarbon monomer unit (X i ) is 60% by mass or more and 82% by mass or less, and the conjugated diene monomer unit (Y i ) is 18 mass % or more and 40 mass % or less. (i-2) Weight average molecular weight (Mw i ) is equal to or greater than 100,000 and equal to or less than 300,000. (i-3) In the dynamic viscoelasticity measurement, the loss tangent value (tan δ) measured at a temperature rise rate of 4° C. / min, a frequency of 1 Hz, and a temperature range of room temperature to 130° C. i ) has at least one maximum value in the temperature range, and the loss tangent value (tan δ i ) is the maximum temperature T i (°C) is in the temperature range of 90°C or more and 120°C or less. (i-4) The vinyl aromatic hydrocarbon monomer unit (X i A hard phase mainly composed of the conjugated diene monomer unit (Y i The soft phase mainly composed of cellulose acetate has a microphase separation structure with a lamellar structure. (ii-1) The mass ratio of the vinyl aromatic hydrocarbon monomer unit (X ii ) to the total (100 mass%) of the vinyl aromatic hydrocarbon monomer unit (X ii ) and the conjugated diene monomer unit (Y ii ) is 70 mass% or more and 84 mass% or less, and the mass ratio of the conjugated diene monomer unit (Y ii ) is 16 mass% or more and 30 mass% or less. (ii-2) The weight average molecular weight (Mw ii ) measured by GPC is 100,000 or more and 300,000 or less. (ii-3) In dynamic viscoelasticity measurement, the loss tangent (tan δ ii ) measured at a heating rate of 4° C. / min, at a frequency of 1 Hz, in the temperature range of room temperature to 130° C. has at least one maximum value in the said temperature range, and the temperature T ii (° C.) at which the loss tangent (tan δ ii ) shows the largest maximum value satisfies the following formulas (1) and (2) in relation to T i (° C.): T i > T ii ... (1) 15≦(T i −T ii )≦35 (2)

2. 2. The heat-shrinkable multilayer film according to claim 1, wherein the block copolymer resin (I) is a block copolymer resin containing a block copolymer having a branched structure.

3. 3. The heat-shrinkable multilayer film according to claim 1, wherein the block copolymer resin (II) is a block copolymer resin containing a block copolymer having a branched structure.

4. The heat shrinkable multilayer film according to any one of claims 1 to 3, wherein the maximum heat shrinkage rate in the MD direction in the temperature range of 70°C or higher and 100°C or lower is 5% or lower and the minimum heat shrinkage rate is -3% or higher.

5. 5. The heat shrinkable multilayer film according to claim 1, which has a heat shrinkage rate in the TD direction at 80°C of 30% or more and a heat shrinkage rate in the TD direction at 100°C of 65% or more.

6. A method for producing the heat-shrinkable multilayer film according to any one of claims 1 to 5, comprising the steps of: An unstretched multilayer film containing the block copolymer resin (I) in at least one surface layer, In the dynamic viscoelasticity measurement, the loss modulus (E″) of the block copolymer resin (I) was measured at a temperature rise rate of 4° C. / min, a frequency of 1 Hz, and in a temperature range of room temperature to 130° C. i ) is the maximum temperature T ic For (T ic -25)℃ or higher (T ic Stretching the unstretched multilayer film in the MD direction at a ratio of 1.00 to 1.30 and in the TD direction at a ratio of 3.0 to 8.0 at a temperature range of 0.15 to 1.5 (+15)°C or lower.

7. A heat-shrinkable label comprising the heat-shrinkable multilayer film according to any one of claims 1 to 5.

8. A method for producing a label by heat shrinking the heat shrinkable label of claim 7.

Citation Information

Patent Citations

  • Heat-shrinkable polymer film

    JP1990227412A

  • Label, bottle fitted with the same and method for regenerating the same

    JP1999231792A

  • Heat-shrinkable film

    JP2003094520A

  • Block copolymer and heat-shrinkable film

    JP2003313259A

  • Block copolymer composition and heat-shrinkable film therefrom

    JP2004099749A